M-Au/TiO2 (M = Ag, Pd, and Pt) nanophotocatalyst for overall solar water splitting: role of interfaces - Melvin, Ambrose A.; Illath, Kavya; Das, Tanmay; Raja, Thirumalaiswamy; Bhattacharyya, Somnath; Gopinath, Chinnakonda S. (Nanoscale, 2015)
M-Au/TiO2 (M = Ag, Pd, Pt) composites were prepared through a facile one-pot photodeposition synthesis and evaluated for solar water splitting (SWS) with and without a sacrificial agent. The M-Au combination exhibits a dominant role in augmenting the H2 generation activity by forming a bi-metallic system. Degussa P25 was used as a TiO2 substrate to photodeposit Au followed by Au + M (M = Ag/Pd/Pt). The SWS activity of the M-Au/TiO2 was determined through photocatalytic H-2 production in the presence of methanol as a sacrificial agent under one sun conditions with an AM1.5 filter. The highest H-2 yield was observed for Pt-0.5-Au-1/TiO2 and was around 1.3 +/- 0.07 mmol h(-1) g(-1), with an apparent quantum yield (AQY) of 6.4%. Pt-0.5-Au-1/TiO2 also demonstrated the same activity for 25 cycles of five hours each for 125 h. Critically, the same Pt-0.5-Au-1/TiO2 catalyst was active in overall SWS (OSWS) without any sacrificial agent, with an AQY = 0.8%. The amount of Au and/or Pt was varied to obtain the optimum composition and it was found that the Pt0.5-Au1/TiO2 composition exhibits the best activity. Detailed characterization by physico-chemical, spectral and microscopy measurements was carried out to obtain an in-depth understanding of the origin of the photocatalytic activity of Pt-0.5-Au-1/TiO2. These in-depth studies show that gold interacts predominantly with oxygen vacancies present on titania surfaces, and Pt preferentially interacts with gold for an effective electron-hole pair separation at Pt-Au interfaces and electron storage in metal particles. The Pt in Pt-0.5-Au-1/TiO2 is electronically and catalytically different from the Pt in Pt/TiO2 and it is predicted that the former suppresses the oxygen reduction reaction.